A Pooled Analysis From Phase 2b and 3 Studies in Japan of Istradefylline in Parkinson's Disease. Issue 8 (5th June 2020) - Hattori, Nobutaka; Kitabayashi, Hiroki; Kanda, Tomoyuki; Nomura, Takanobu; Toyama, Keizo; Mori, Akihisa
Abstract: Background: Characterization of patient factors associated with istradefylline efficacy may facilitate personally optimized treatment. Objectives: We aimed to examine which patient factors are associated with favorable istradefylline treatment outcomes in PD patients with motor complications. Methods: We performed a pooled analysis of data from two identical phase 2b and 3 Japanese studies of istradefylline. Logistic regression models were used to assess the association of 12 patient characteristics with favorable outcomes. Results: Off time reduction and increased good on time with istradefylline provided a significantly favorable response in patients aged ≥65 years. Off time reduction was more favorable in patients with ≥8‐hour daily off time at baseline. Improvement in UPDRS Part III was favorable in patients with UPDRS Part III baseline score ≥ 20. Conclusions: Several patient factors influenced the effect of istradefylline on motor fluctuations, motor function, activities of daily living, and clinical impression. © 2020 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.